Understanding tourists’ ambassador role of their origin places from perspective of residents’ attitudes towards tourists - Juan Bi; Chunxia Gu (Scientific Reports)
Abstract Recognizing the pivotal role of tourists as ambassadors for their hometown is imperative, as it relates to the dynamic host-guest relationship, thereby significantly influencing the sustainable tourism progress in both their originating locations and the visited destinations. To delve deeper into this ambassadorial role, this study employed the tripartite model of resident attitude, which bridges the intricate interplay between residents’ cognitive, affective, and conative attitudes towards tourists. 204 U.S. people have been enrolled through Amazon’s Mechanical Turk to finish semi-structured questionnaire about their attitudes towards Chinese outbound tourists. Leximancer, a computer-assisted qualitative data analysis approach was applied. Results demonstrated that neutral or positive cognitive-attitudes U.S. residents held towards Chinese tourists exceeded negative cognitive attitudes. Further analysis inferred that it was the interpretation or attribution of cognitive attitudes that would induce residents’ different emotional feelings and behavioral intention. Positive interpretation would lead to positive feeling (i.e., admiration) and positive intention to visit China. Negative interpretation would lead to negative feeling (i.e., contempt) and negative intention to visit China. This research provided implications for destination management organization of tourists’ origin place to incorporate outbound tourists as their place ambassadors.